Teaching technology - Banks, Frank (Routledge in association with the Open University, 1994)
Technology is a new and rapidly changing area of the curriculum. For experienced teachers in school as well as for students and novices, it has involved the need for a whole new range of knowledge and skills in teaching. This reader draws together already published articles and newly commissioned material from leading authors in the field to help teachers at all stages of their professional development to understand the principles which need to be considered whatever the detail of the National Curriculum in this subject. It looks at the development of technology as a school subject, at the ways in which pupils learn and teachers teach it, and at its place within the wider contexts of education as a whole and of the society which technological developments help to shape.